Identification of an Actual Strain-Induced Effect on Fast Ion Conduction in a Thin-Film Electrolyte - Ahn, Junsung; Jang, Ho Won; Ji, Hoil; Kim, Hyoungchul; Yoon, Kyung Joong; Son, Ji-Won; Kim, Byung-Kook; Lee, Hae-Weon; Lee, Jong-Ho (AMER CHEMICAL SOC, 2018)
Strain-induced fast ion conduction has been a research area of interest for nanoscale energy conversion and storage systems. However, because of significant discrepancies in the interpretation of strain effects, there remains a lack of understanding of how fast ionic transport can be achieved by strain effects and how strain can be controlled in a nanoscale system. In this study, we investigated strain effects on the ionic conductivity of Gd0.2Ce0.8O1.9-delta (100) thin films under well controlled experimental conditions, in which errors due to the external environment could not intervene during the conductivity measurement. In order to avoid any interference from perpendicular-to-surface defects, such as grain boundaries, the ionic conductivity was measured in the out-of-plane direction by electrochemical impedance spectroscopy analysis. With varying film thickness, we found that a thicker film has a lower activation energy of ionic conduction. In addition, careful strain analysis using both reciprocal space mapping and strain mapping in transmission electron microscopy shows that a thicker film has a higher tensile strain than a thinner film. Furthermore, the tensile strain of thicker film was mostly developed near a grain boundary, which indicates that intrinsic strain is dominant rather than epitaxial or thermal strain during thin-film deposition and growth via the Volmer-Weber (island) growth mode.
Keywords: OXIDE FUEL-CELLS; DOPED CERIA; ELECTROCHEMICAL PROPERTIES; NANOCRYSTALLINE CERIA; ELECTRICAL-PROPERTIES; TRANSPORT-PROPERTIES; SOLID ELECTROLYTES; THERMAL-EXPANSION; OXYGEN DIFFUSION; LATTICE-STRAIN